1999
DOI: 10.1111/j.2042-3306.1999.tb05210.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of exercise variables measured during intensity of simulated training to variables at maximal effort in Standardbreds

Abstract: Summary The heart rate changes during routine training in a group of 8 actively racing Standardbreds were used to simulate the training work on a treadmill (ST) and indices of exercise compared to maximal effort (MAX) on the treadmill. The following parameters were recorded during treadmill work: heart rate, velocity, O2 consumption, respiratory and stride frequency, and stride length. Blood lactate concentrations were measured before and after each work test. Heart rate during simulated training was mean ± s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Most conditioning workouts in horses have been directed by the particular event for which the horses have trained (Evans et al 1993), but are still assessed qualitatively. For example, workouts for Standardbred horses usually involve a work intensity that is dictated by the driver's experience and the horse's willingness to work (Pringle et al 1999). It has been suggested that the efficiency of current training is a major limiting factor of performance in racehorses (von Wittke et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most conditioning workouts in horses have been directed by the particular event for which the horses have trained (Evans et al 1993), but are still assessed qualitatively. For example, workouts for Standardbred horses usually involve a work intensity that is dictated by the driver's experience and the horse's willingness to work (Pringle et al 1999). It has been suggested that the efficiency of current training is a major limiting factor of performance in racehorses (von Wittke et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate, oxygen consumption and lactate accumulation with exercise are quantitative factors that can evaluate progress (Persson 1983;Pringle et al 1999). The running speed-heart rate relationship (v HR ) is easily measured and reproducible and can be applied under field conditions (Couroucé et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, workouts for Standardbred horses usually involve a work intensity that is dictated by the driver's experience and the horse's willingness to work (Pringle et al, 1999). Thoroughbred racehorse training has remained basically the same over the last 60 years and therefore it has been suggested that the efficiency of current training may be a major limiting factor of performance in racehorses (von Wittke et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Only more recently have training programmes evolved to use more quantitative assessments of horses' athletic improvement. Heart rate, oxygen consumption and lactate accumulation with exercise are quantitative factors that can evaluate progress (Persson 1983;Pringle et al 1999). The running speed-heart rate relationship is easily measured and reproducible and can be applied under field conditions (Couroucé et al, 2000).…”
Section: Introductionmentioning
confidence: 99%